School desegregation, school re-zoning, and growth management in two Maryland counties - Bierbaum, Ariel H.; Sunderman, Gail L. (Education Policy Analysis Archives, 2021)
This article examines how school and non-school policies interact to reinforce or disrupt school segregation in the context of suburban communities and how these systems are maintained by structural and institutional mechanisms. Methodologically, we use a case study approach to delve deeply into the interpretation and implementation of school attendance zone redesign and non-school policies, specifically land use policies and tools. We draw on neo-institutionalist theory and Ray’s (2019) framework of racialized organizations to make sense of school districts, planning agencies, and their policies. We find that school district rezoning policies provide a weak regulatory framework for desegregating schools because school zoning decisions are not made in a vacuum but rather are shaped by policies and actions taken by other actors in a multi-level governance structure. School zoning policies themselves prioritized capacity over desegregation, and regulations and norms governing the public engagement processes privilege opposition to desegregation. Our study points to the importance of greater coordination across governmental levels and policy arenas, and underscores how desegregation policy is part of a political and relational process between advocates, elected leaders, families, and youth across policy sectors.